Pengamatan Pertumbuhan Jamur Rhizopus oligosporus dari Tempe pada Media PDA Menggunakan Metode Pengenceran - Lisa Fitriana; Ardi Mustakim (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Tempe is a fermented soybean product widely known in Indonesia and various countries, with Rhizopus oligosporus fungus as the main microorganism involved in the fermentation process. This study aims to observe the growth of Rhizopus oligosporus fungus isolated from tempeh using the dilution method and grown on Potato Dextrose Agar (PDA) media. The research process began with taking tempeh samples which were then subjected to serial dilutions. Next, the diluted samples were inoculated into PDA media and incubated at 37°C to facilitate fungal growth. Observations were made periodically to monitor the development of fungal colonies and the morphology formed. In the observation, it was found that Rhizopus oligosporus fungal colonies growing on PDA media were grayish-white with a distinctive filamentous hyphal structure. This indicates that PDA media strongly supports the growth of the fungus. In addition, the dilution method used in this study proved effective in separating fungal colonies, thus facilitating the morphological identification of each colony. The serial dilution method is very important in isolating microorganisms present in tempeh samples. By separating the fungal colonies from each other, researchers can observe the development of each colony more clearly and accurately. The results of this study indicate that PDA media is very suitable for supporting the growth of Rhizopus oligosporus and that the serial dilution method is an effective way to isolate this fungus from tempeh. In conclusion, this study proves that serial dilution followed by inoculation on PDA media is an effective method in observing and isolating Rhizopus oligosporus from tempeh. PDA media is able to support optimal fungal growth and allows for clear observation of the colonies and their morphology.